High risk coronavirus disease 2019: The primary results of the CoronaHeart multi-center cohort study. (October 2021) - Guimarães, Patrícia O.; de Souza, Francis R.; Lopes, Renato D.; Bittar, Cristina; Cardozo, Francisco A.; Caramelli, Bruno; Calderaro, Daniela; Albuquerque, Cícero P.; Drager, Luciano F.; Feres, Fausto; Baracioli, Luciano; Feitosa Filho, Gilson; et al.
Abstract: Background: Patients with Coronavirus Disease 2019 (COVID-19) may present high risk features during hospitalization, including cardiovascular manifestations. However, less is known about the factors that may further increase the risk of death in these patients. Methods: We included patients with COVID-19 and high risk features according to clinical and/or laboratory criteria at 21 sites in Brazil from June 10th to October 23rd of 2020. All variables were collected until hospital discharge or in-hospital death. Results: A total of 2546 participants were included (mean age 65 years; 60.3% male). Overall, 70.8% were admitted to intensive care units and 54.2% had elevated troponin levels. In-hospital mortality was 41.7%. An interaction among sex, age and mortality was found (p = 0.007). Younger women presented higher rates of death than men (30.0% vs 22.9%), while older men presented higher rates of death than women (57.6% vs 49.2%). The strongest factors associated with in-hospital mortality were need for mechanical ventilation (odds ratio [OR] 8.2, 95% confidence interval [CI] 5.4–12.7), elevated C-reactive protein (OR 2.3, 95% CI 1.7–2.9), cancer (OR 1.8, 95 %CI 1.2–2.9), and elevated troponin levels (OR 1.8, 95% CI 1.4–2.3). A risk score was developed for risk assessment of in-hospital mortality. Conclusions: This cohort showed that patients with COVID-19 and high risk features have an elevated rate of in-hospital mortality with differences according to age and sex. These results highlight unique aspects of this population and might help identifying patients who may benefit from more careful initial surveillance and potential subsequent interventional therapies.